OPTIMALISASI KOMPETENSI MENULIS AKADEMIK MELALUI PELATIHAN SITASI MAHASISWA STIE MUHAMMADIYAH KALIANDA - Sengaji, Zulfahmi (MUHKAL, 2024)
Writing scientific papers is an integral part of academic tasks for students. Furthermore, research activities are also a key focus of universities. However, many students face difficulties in creating accurate references and bibliographies. Therefore, the aim of this community service is to provide support and strengthen the competencies of students in scientific writing, particularly in terms of referencing and bibliography writing. This training can significantly benefit the participants by improving their scientific writing skills, and it is expected that students can apply the skills they acquire from this training to produce high-quality scientific works. Tuliskan abstrak dalam bahasa Inggris